International Finance / The Markets and Financial Management of Multinational Business - Levi D. Maurice (Mcgraw Hill, Inc, 1996)
Preface, The World of International Finance, The Markets for Foreign Exchange, Determination of Exchange Rates, The Fundamental International Parity Conditions, Managing Foreign Exchange Risk and Exposure, International Investment and Financing, Institutional Structure of International Trade and Finance, Summary, Bibliography, Name and Subject Index.